Ricky Ricotta's Mighty Robot vs. the Uranium Unicorns from Uranus : Ricky Ricotta #7 - Pilkey, Dav, 1966-; Santat, Dan (New York, NY : Scholastic Inc., 2014)
Evil Uncle Unicorn attempts to dominate earth by using a Ladybot to trick Mighty Robot.
Originally published in 2005 in a slightly different form by Blue Sky Press.
Keywords: Ricotta, Ricky (Fictitious character) -- Juvenile fiction; Mice -- Juvenile fiction; Robots -- Juvenile fiction; Heroes -- Juvenile fiction; Friendship -- Juvenile fiction; Unicorns -- Juvenile fiction; Mice -- Fiction; Robots -- Fiction; Heroes -- Fiction; Uranus (Planet) -- Juvenile fiction; Humorous fiction